Quaternary Ammonium Compounds as Candidate Photoprotective Compounds in Reef-Building Corals - Hill, Richard W. (Frontiers in Marine Science, 2022)
Quaternary ammonium compounds (QACs) – e.g., betaines – have a chemical structure related to that of the tertiary sulfonium compounds (TSCs) – e.g., dimethylsulfoniopropionate – explaining why these two classes of coral metabolites are often studied and interpreted together. Functionally, both QACs and TSCs play important roles in the photobiology of reef-building corals under stress, according to recent hypotheses. The TSC dimethylsulfoniopropionate (DMSP) is the principal precursor of the gas dimethylsulfide (DMS) which is hypothesized to affect, through influences on cloud formation, the photon and thermal fluxes to which corals are exposed. Simultaneously, QACs – e.g., glycine betaine – in coral tissues are hypothesized to protect the zooxanthellae photosystems against photon and thermal stresses by exerting stabilizing effects on photosystem proteins and by ameliorating reactive-oxygen-species perturbations. This review, which synthesizes the most current available evidence on the relevant actions of QACs, emphasizes the need for enhanced direct study of QAC physiology in corals to ascertain the degree to which coral QACs exert photoprotective effects paralleling their well-established protective effects in plants.